2016
DOI: 10.1007/s10719-016-9686-y
|View full text |Cite|
|
Sign up to set email alerts
|

AGE-RAGE interaction in the TGFβ2-mediated epithelial to mesenchymal transition of human lens epithelial cells

Abstract: Basement membrane (BM) proteins accumulate chemical modifications with age. One such modification is glycation, which results in the formation of advanced glycation endproducts (AGEs). In a previous study, we reported that AGEs in the human lens capsule (BM) promote the TGFβ2-mediated epithelial-to-mesenchymal transition (EMT) of lens epithelial cells, which we proposed as a mechanism for posterior capsule opacification (PCO) or secondary cataract formation. In this study, we investigated the role of a recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 65 publications
1
16
1
Order By: Relevance
“…In an potentially related area, it is interesting to note that fructose, the end product of AR polyol pathway, has been demonstrated to form advanced glycated end-products (AGEs) much faster than glucose [35]. Raghavan and colleagues recently reported that AGEs in lens capsule enhance EMT of LECs under TGF-β2 treatment [36, 37]. Accordingly, AR-induced AGEs production might be another stimulus for PCO development following cataract surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In an potentially related area, it is interesting to note that fructose, the end product of AR polyol pathway, has been demonstrated to form advanced glycated end-products (AGEs) much faster than glucose [35]. Raghavan and colleagues recently reported that AGEs in lens capsule enhance EMT of LECs under TGF-β2 treatment [36, 37]. Accordingly, AR-induced AGEs production might be another stimulus for PCO development following cataract surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The fetal human lens epithelial cell line (FHL124) was kindly provided by Prof. Michael Wormstone (School of Biological Sciences, University of East Anglia, UK, originally from Prof. John Reddan, Oakland University, MI). FHL124 cells were cultured as previously described [38] and treated with aspirin (Sigma-Aldrich, St. Louis, MO, Cat# A5376) at 2 mM for 24 h and then cotreated with 10 ng/ml TGFβ2 (Peprotech, Inc., Rocky Hill, NJ, Cat# 100-35B,10 ng/ml) for the additional indicated times. The MTT assay was used to determine the cytotoxicity of aspirin or cell proliferation.…”
Section: Treatment Of Human Lecs With Tgf2mentioning
confidence: 99%
“…The Maillard reaction of protein glycation and its involvement in the pathogenesis of diabetic complications has been thoroughly investigated. 1,2 In addition to protein glycation, amino lipids, such as phosphatidylethanolamine (PE) and phosphatidylserine (PS), could be involved in the Maillard reaction with reducing sugars, due to their free amino group. 3,4 In vivo studies demonstrated that membrane phospholipids such as PE were abnormally glycated under hyperglycemic conditions, which led to destruction of cellular integrity and functionality.…”
Section: Introductionmentioning
confidence: 99%